Basicity as a Thermodynamic Descriptor of Carbanions Reactivity with Carbon Dioxide: Application to the Carboxylation of α,β-Unsaturated Ketones - Franceschi, Pietro; Nicoletti, Catia; Bonetto, Ruggero; Bonchio, Marcella; Natali, Mirco; Dell’Amico, Luca; Sartorel, Andrea (Frontiers in Chemistry, 2021)
The utilization of carbon dioxide as a raw material represents nowadays an appealing strategy in the renewable energy, organic synthesis, and green chemistry fields. Besides reduction strategies, carbon dioxide can be exploited as a single-carbon-atom building block through its fixation into organic scaffolds with the formation of new C-C bonds (carboxylation processes). In this case, activation of the organic substrate is commonly required, upon formation of a carbanion C−, being sufficiently reactive toward the addition of CO2. However, the prediction of the reactivity of C− with CO2 is often problematic with the process being possibly associated with unfavorable thermodynamics. In this contribution, we present a thermodynamic analysis combined with density functional theory calculations on 50 organic molecules enabling the achievement of a linear correlation of the standard free energy (ΔG0) of the carboxylation reaction with the basicity of the carbanion C−, expressed as the pKa of the CH/C− couple. The analysis identifies a threshold pKa of ca 36 (in CH3CN) for the CH/C− couple, above which the ΔG0 of the carboxylation reaction is negative and indicative of a favorable process. We then apply the model to a real case involving electrochemical carboxylation of flavone and chalcone as model compounds of α,β-unsaturated ketones. Carboxylation occurs in the β-position from the doubly reduced dianion intermediates of flavone and chalcone (calculated ΔG0 of carboxylation in β = −12.8 and −20.0 Kcalmol-1 for flavone and chalcone, respectively, associated with pKa values for the conjugate acids of 50.6 and 51.8, respectively). Conversely, the one-electron reduced radical anions are not reactive toward carboxylation (ΔG0 > +20 Kcalmol-1 for both substrates, in either α or β position, consistent with pKa of the conjugate acids < 18.5). For all the possible intermediates, the plot of calculated ΔG0 of carboxylation vs. pKa is consistent with the linear correlation model developed. The application of the ΔG0 vs. pKa correlation is finally discussed for alternative reaction mechanisms and for carboxylation of other C=C and C=O double bonds. These results offer a new mechanistic tool for the interpretation of the reactivity of CO2 with organic intermediates.